ENGLISH PROFICIENCY TEST UNTUK MENINGKATKAN KEMAMPUAN BAHASA INGGRIS DASAR DI LKP BIG DREAM DRAJAD LAMONGAN - Farokhah, Fiqih Aisyatul; Latifah, Eny (Jurnal Pengabdian Masyarakat Berkarya, 2024)
The objective of this community service activity is to enhance the fundamental English competencies of students and college students through training and the simulation of the English Proficiency Test (EPT) at LKP BIG DREAM, Drajad, Lamongan. The training was conducted in a face-to-face manner, employing a participatory approach that emphasized the active involvement of participants in each session. The materials concentrated on aspects of grammar, vocabulary, listening, and reading comprehension. The final evaluation of the study involved EPT simulation, which was utilized to assess the enhancement of participants' competence. The findings of the activity demonstrated an enhancement in post-test scores in comparison to the pre-test, along with an augmentation in the participants' confidence in their comprehension and utilization of English. Participant and partner reflections indicated a favorable response to the training method employed. This initiative not only enhances individual competencies but also reinforces the collaborative efforts between universities and non-formal training institutions in addressing local human resource development needs.